MORPHOLOGICAL CHANGES OF THE RAT OFFSPRINGS’ KIDNEYS IN DIABETES MELLITUS CAUSED BY STREPTOZOTOCIN - Ikrom Tilyabov; Ravshan Usmanov; Ilich Gulmanov; Suhrob Ergashev (Central Asian Journal of Medicine, 2024)
In children, usually type 1 diabetes mellitus ( DM), more often type 2 occurs. Advanced hyperglycemic nephropathies (HN), such as loss of filtration rate (LFR) in nephron, do not occur until puberty, renal biopsies show structural changes of HN within 1.5-5 years of onset of Type 1 DM. The earliest clinical sign of HN, such as increased albumin excretion in the urine, usually occurs in childhood and adolescence, and is an important opportunity to detect and treat early HN. Research on the issue of Type 1 diabetes has shown that HN is typical of a part of people with diabetes who are at high risk of early death, which increases the ability to detect, prevent and treat HN. Preliminary studies suggest that type 2 DM, which began in young adults, is associated with a higher prevalence of risk factors. Type 2 DM initiated in young people helps to conduct scientific research on a deeper understanding of risk factors, underlying mechanisms, and treatment options for HN.